The subjective-objective constitution of objectivity’s structure: A lecture on recognition synthesis in the concept - López López, Alberto (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The general aim of the following paper is to show, through a specific lecture, that the fundament of objectivity’s structure exposed in the Transcendental Deduction (and, more concretely, in the synthesis of recognition of the concept) is the figurative synthesis (synthesis speciosa) of the productive imagination. In order to fulfill this aim, a lecture on the third aspect of the synthesis is proposed, where the subjective-objective constitution of the mentioned structure works as the guiding thread showing that the Kantian argumentation in this passage proceeds oscillating between its subjective and objective poles. In line with it, the hypothesis of work is that, in order to acquire a comprehension about the fundament sought by Transcendental Deduction and, therefore, about the objectivity’s structure proposed by it, it is indispensable to heed the subjective-objective character of the mentioned structure.
Keywords: subject; objectivity; position; self-position; synthesis; transcendental; recognition; concept; imagination